(untitled) (Research, Society and Development, 2022)
Currently, there is no drug that has proven neuroprotective properties in Parkinson’s disease. The best-known drug is levodopa, which acts as inhibitors of the MAO-B and COMT enzymes involved in dopamine degradation. Although levodopa is the "gold standard" of treatment, as the disease progresses, most patients develop complications from the therapy and side effects. In this sense, the combination of two abundant substances and phytotherapics as alternatives to the use of traditional medicines is approached, namely Zingerone and Gamma-Mangostin. In which they presented favorable results in molecular docking.